AKTIVITAS ANTIBAKTERI KOMBINASI EKSTRAK DAUN PEPAYA DAN KULIT JERUK MANIS TERHADAP BAKTERI Propionibacterium acne PENYEBAB JERAWAT SECARA IN-VITRO - Agung Nur Cahyanta; Osie Listina; Dini Cahya Chairunnisa (Parapemikir : Jurnal Ilmiah Farmasi, 2020)
Propionibacterium acne plays a role in causing zits because there are forming blackheads and the inflammation stimulated by bacterial metabolic products. Acne treatment is usually treated by antibiotic which can kill the bacteria like tetracycline and erythromycin. The use of antibiotic in a long term can cause resistance, organ damage and hypersensitivity reactions so that it needs other antibiotics. The research aimed to find out the effectiveness of the combination of papaya leaf extract and sweet orange peel compared to single extract to inhibit the bacterial growth. The extraction was performed by ethanol 96%; the extraction result was the yield of papaya leaf 14.4% and sweet orange peel 19.4%; the total ash content of papaya leaf extract was 8% and sweet orange peel of 10%. The phytochemical screening of papaya leaf extract and sweet orange peel contained positively flavonoid, alkaloid, saponin, and tannin. The antibacterial activity of average inhibition zone diameter on the ratio of papaya leaf extract and orange peel extract (2 : 2) was 7.15 mm; ratio of 1 : 3 was 10.08 mm; ratio of  3 : 1 was 5.58 mm; ratio of 4 : 0 was 5.41 mm and ratio of 0 : 4 was 7.41 mm.  The result of One Way ANOVA described that the average of inhibition zone diameter in each treatment had significantly difference (p0.05). The result of the advanced test, LSD (Least Significance Different), showed that the comparison of inhibition zone diameter between papaya leaf extract and orange peel extract was 1 : 3, compared to all group had a real difference (p0.05). Based on the result, it can be concluded that the ratio was more effective to inhibit the activity of Propionibacterium acne than another solution test both single and combination.Keyword : Papaya leaf, Sweet orange peel, Combination, Acne, Propionibacterium acnes